Step-by-step explanation:
1/2 is the answer
hope it helps
thank you
Answer:
x=0 x=3 x=-2
Step-by-step explanation:
p(x)= 3x^3 – 3x^2– 18x
Factor out the greatest common factor, 3x
p(x)= 3x (x^2 – x– 6)
Factor inside the parentheses
What 2 numbers multiplies to -6 and adds to -1
-3*2 = -6
-3+2 = -1
p(x)= 3x (x-3)(x+2)
Setting the function equal to zero to find the zeros
0 = 3x (x-3)(x+2)
Using the zero product property
3x = 0 x-3 =0 x+2 =0
x=0 x=3 x=-2
Answer:
150 degrees
Step-by-step explanation:
5 + 1 = 6
180 : 6 = 30
30 x 5 = 150
Answer: Choice D
(x - 8) and (x - 3)
===============================================
Explanation:
The term "root" is the same as "zeros of a function".
If 3 is a root, then x = 3 leads to x-3 = 0 after subtracting 3 from both sides.
If 8 is a root, then x = 8 leads to x-8 = 0 for similar reasoning
Use of the zero product property allows us to combine those two rules into the following
(x-3)(x-8) = 0
This shows that the two factors are (x-8) and (x-3)
The order of the factors doesn't matter because we can multiply two numbers in any order.